Menjembatani Teknologi dan Spiritualitas: Model Holistik Profesionalisme Guru Pendidikan Agama Kristen dalam Pembelajaran Digital - Marsiana Yupi; Ruhut Parningotan Tambunan; Mesida Ndruru (STT Kristus Alfa Omega, 2026)
This study aims to analyze the professionalism of Christian Religious Education teachers in addressing pedagogical challenges in the era of digital learning, as well as strategies to strengthen it in fostering students’ character and spirituality. The method used is descriptive qualitative research through a literature review, examining various relevant scientific sources. The results of the literature review indicate that digital transformation promotes more interactive, collaborative, and flexible learning; however, it also presents challenges in the form of limited digital literacy among teachers, a decline in the depth of pedagogical relationships, and the risk of a reduction in spiritual values in online learning. This study offers a model of holistic Christian Religious Education teacher professionalism that integrates theological, pedagogical, digital, and spiritual dimensions as a conceptual framework to strengthen reflective learning, Christian character formation, and contextual faith development in the digital age. In conclusion, the judicious and contextual integration of technology can support the creation of transformative, relevant, and holistic Christian Religious Education.